Known unknowns: Examining the burden of neurocognitive impairment in the end‐stage renal failure population. Issue 6 (10th June 2018) - Wilson, Scott; Dhar, Arup; Tregaskis, Peter; Lambert, Gavin; Barton, David; Walker, Rowan
ABSTRACT: The burden of neurocognitive impairment (NCI) in patients receiving maintenance dialysis represents a spectrum of deficits across multiple cognitive domains that are associated with hospitalization, reduced quality‐of‐life, mortality and forced decision‐making around dialysis withdrawal. Point prevalence data suggest that dialysis patients manifest NCI at rates 3‐ to 5‐fold higher than the general population, with executive function the most commonly affected cognitive domain. The unique physiology of the renal failure state and maintenance dialysis appears to drive an excess of vascular dementia subtype compared to the general population where classical Alzheimer's disease predominates. Despite the absence of evidence‐based cost‐effective therapies for NCI, detecting it in this population creates opportunity to proactively personalize care through education, supported decision making and targeted communication strategies to cover specific areas of deficit and help define goals of care. This review discusses NCI in the dialysis setting, including developments in the definition of neurocognitive impairment, dialysis‐specific epidemiology across modalities, screening strategies and opportunities for dialysis providers in this space. Summary at a Glance: This paper reviews neurocognitive impairment in ESRD patients. This issue is increasingly recognized and is becoming clinically important.